Grain size‐sensitive viscoelastic relaxation and seismic properties of polycrystalline MgO. Issue 7 (13th July 2016) - Barnhoorn, A.; Jackson, I.; Fitz Gerald, J. D.; Kishimoto, A.; Itatani, K.
Abstract: Torsional forced‐oscillation experiments on a suite of synthetic MgO polycrystals, of high‐purity and average grain sizes of 1–100 µm, reveal strongly viscoelastic behavior at temperatures of 800–1300°C and periods between 1 and 1000 s. The measured shear modulus and associated strain energy dissipation both display monotonic variations with oscillation period, temperature, and grain size. The data for the specimens of intermediate grain size have been fitted to a generalized Burgers creep function model that is also broadly consistent with the results for the most coarse‐grained specimen. The mild grain size sensitivity for the relaxation time τ L, defining the lower end of the anelastic absorption band, is consistent with the onset of elastically accommodated grain boundary sliding. The upper end of the anelastic absorption band, evident in the highest‐temperature data for one specimen only, is associated with the Maxwell relaxation time τ M marking the transition toward viscous behavior, conventionally ascribed a stronger grain size sensitivity. Similarly pronounced viscoelastic behavior was observed in complementary torsional microcreep tests, which confirm that the nonelastic strains are mainly recoverable, i.e., anelastic. With an estimated activation volume for the viscoelastic relaxation, the experimentally constrained Burgers model has been extrapolated to the conditions of pressure and temperature prevailing in the Earth's uppermost lower mantle. For a plausible grain size of 10 mm, the predicted dissipation Q −1 ranges from ~10 −3 to ~10 −2 for periods of 3–3000 s. Broad consistency with seismological observations suggests that the lower mantle ferropericlase phase might account for much of its observed attenuation. Key Points: High‐temperature viscoelastic relaxation in polycrystalline MgO has been quantified Shear modulus and dissipation are broadly consistent with the theory of grain boundary sliding Extrapolation suggests that ferropericlase might contribute to attenuation in the lower mantle